Temperature Anomaly and Vector-Borne Disease Incidence - Park, Alexander (Technium BioChemMed, 2021)
This study looks into whether three common vector-borne diseases, such as malaria, dengue fever, and Lyme disease, are connected to temperature anomaly, with an emphasis on high-incidence areas. First, malaria study findings reveal a significant positive association between disease prevalence and temperature anomaly in a sample of the seven most common countries in the Sahara desert and portions of Oceania. Second, study results for dengue fever show a strong positive connection between disease incidence and temperature anomaly, in Asian countries like Vietnam and the Philippines. Finally, research on Lyme disease in the United States indicates that there is a significant positive association between temperature anomaly and disease incidence not just in high-incidence areas, but also in neighboring states. In conclusion, temperature anomaly may enhance the incidence of all three infectious diseases investigated in this study, according to the findings.